2020
DOI: 10.1371/journal.ppat.1008429
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 inhibition exerts anti-viral activity through DNA damage-dependent innate immune responses

Abstract: Chromatin dynamics regulated by epigenetic modification is crucial in genome stability and gene expression. Various epigenetic mechanisms have been identified in the pathogenesis of human diseases. Here, we examined the effects of ten epigenetic agents on pseudorabies virus (PRV) infection by using GFP-reporter assays. Inhibitors of bromodomain protein 4 (BRD4), which receives much more attention in cancer than viral infection, was found to exhibit substantial anti-viral activity against PRV as well as a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 75 publications
2
68
2
Order By: Relevance
“…Unlike the functions of the BRD2/ET domain interacting with KSHV LANA and MLV integrase, NDV undergoes genomic replication, mRNA transcription, protein synthesis, and assembly of virus components in the cytoplasm, but the NDV M-chBRD2/ET interaction in the nucleus mainly assists in viral RNA synthesis and transcription until later in infection. Currently, accumulating studies have also revealed that the BRD2, BRD3 and BRD4 proteins participate in the host immune response against virus infection [ 51 53 ]. In our recent studies using quantitative proteomics analysis, we found that the parental virus rSS1GFP but not the mutant virus rSS1GFP-M/NLSm harbouring an NLS mutation in the M protein reduced the expression of the BRD2, BRD3 and BRD4 proteins to different degrees in virus-infected cells, suggesting that the decreased expression of BRD2, BRD3 and BRD4 was caused by early nuclear localization of the M protein [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the functions of the BRD2/ET domain interacting with KSHV LANA and MLV integrase, NDV undergoes genomic replication, mRNA transcription, protein synthesis, and assembly of virus components in the cytoplasm, but the NDV M-chBRD2/ET interaction in the nucleus mainly assists in viral RNA synthesis and transcription until later in infection. Currently, accumulating studies have also revealed that the BRD2, BRD3 and BRD4 proteins participate in the host immune response against virus infection [ 51 53 ]. In our recent studies using quantitative proteomics analysis, we found that the parental virus rSS1GFP but not the mutant virus rSS1GFP-M/NLSm harbouring an NLS mutation in the M protein reduced the expression of the BRD2, BRD3 and BRD4 proteins to different degrees in virus-infected cells, suggesting that the decreased expression of BRD2, BRD3 and BRD4 was caused by early nuclear localization of the M protein [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Outside of human herpesviruses, a study on the swine alphaherpesvirus pseudorabies virus (PRV) has identified various means by which BRD4 inhibition can affect lytic virus infection. Use of three different compounds (JQ1, OTX015, and iBET-151), alongside confirmatory data with siRNA use, has recently shown that inhibition of BRD4, due to its importance in maintenance of higher-order chromatin structure (Wang et al, 2012 ), can lead to activation of the DNA damage response by chromatin de-compaction (Wang et al, 2020 ). In concert with induction of interferon-stimulated genes (ISGs), including IFN-β, DNA damage triggers activation of cGAS-mediated innate immunity and is able to attenuate attachment of the virus to the surface of BRDi-treated cells (Wang et al, 2020 ).…”
Section: Bet Bromodomain Inhibition and Alphaherpesvirusesmentioning
confidence: 93%
“…Use of three different compounds (JQ1, OTX015, and iBET-151), alongside confirmatory data with siRNA use, has recently shown that inhibition of BRD4, due to its importance in maintenance of higher-order chromatin structure (Wang et al, 2012 ), can lead to activation of the DNA damage response by chromatin de-compaction (Wang et al, 2020 ). In concert with induction of interferon-stimulated genes (ISGs), including IFN-β, DNA damage triggers activation of cGAS-mediated innate immunity and is able to attenuate attachment of the virus to the surface of BRDi-treated cells (Wang et al, 2020 ). In the absence of any effects to virus transcription, this BRDi-driven induction of an anti-viral state caused not only restriction of PRV infection in cell lines but also in an in vivo mouse model (Wang et al, 2020 ).…”
Section: Bet Bromodomain Inhibition and Alphaherpesvirusesmentioning
confidence: 93%
See 1 more Smart Citation
“…The development of site-specific histone deacetylase (HADC) inhibitors, bromodomain inhibitors, histone lysine methyltransferase (HKMT) inhibitors represent new tools in the modulation of histone post-translational modifications. The HDAC inhibitors were found to be a promising approach to purge the reservoir of persistent HIV infection [ 119 ], whereas inhibitors of bromodomain protein 4 (BRD4) exhibited substantial anti-viral activity against pseudorabies virus as well as a wide range of DNA and RNA viruses [ 120 ]. Furthermore, improved understanding of clustered regularly interspaced short palindromic repeats (CRISPR) editing system enabling targeted modification of the epigenomemay result in expanded applications in the field of infectious diseases providing clarification of host and microbe interactions and help in the prevention and treatment of infectious diseases [ 121 ].…”
Section: Epigenetic Modifications As Therapeutic Targetsmentioning
confidence: 99%